2010
DOI: 10.1103/physreva.82.013802
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced dynamics in the Lorentz oscillator model with magnetic forces

Abstract: The classical Lorentz oscillator model of bound electron motion ordinarily excludes magnetic forces at nonrelativistic intensities for the simple reason that their magnitude is small. However, perturbative and numerical results show that when the v × B term is retained, dynamically enhanced terms give rise to large amplitude, magnetically induced charge displacements at zero frequency and at twice the driving frequency in the Cartesian laboratory frame. Numerical simulations of electron motion are in accord wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…This phenomenon manifests itself in Eqs. (31) and (42) through the doubled-frequency detuning parameter ⌬ 2 , but its impact only becomes apparent in numerical simulations [16]. The result of this dynamic enhancement is that magnetic dipole response can be nearly as intense as the electric response at intensities far below the relativistic threshold [21] due to transfer of energy between the motions associated with the E and B components of the light field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon manifests itself in Eqs. (31) and (42) through the doubled-frequency detuning parameter ⌬ 2 , but its impact only becomes apparent in numerical simulations [16]. The result of this dynamic enhancement is that magnetic dipole response can be nearly as intense as the electric response at intensities far below the relativistic threshold [21] due to transfer of energy between the motions associated with the E and B components of the light field.…”
Section: Resultsmentioning
confidence: 99%
“…(33) at nonrelativistic intensities. This may be demonstrated by direct numerical integration of the equations of motion [15] and is the subject of a forthcoming publication [16]. Ultrafast growth (on a timescale ⌬t Ͻ 100 fs [1,3]) of magnetic response takes place via energy transfer from electric field-induced linear motion along x, to the azimuthal motion initiated by the magnetic field along Ј, and is due to the phenomenon of parametric resonance [17].…”
Section: ͑32͒mentioning
confidence: 99%
“…Perturbative solutions of these equations, correct to first order in the weak optical magnetic field, 6 are…”
Section: A Classical Approachmentioning
confidence: 99%
“…5 It appears at sub-relativistic intensities due to parametric enhancement. Classical analysis, 2 numerical simulations and perturbation theory, 6 as well as quantum theory 7 of this phenomenon -transverse optical magnetism -have now been published. These treatments describe charge oscillations that are driven jointly by the electric and magnetic field components of a linearly-polarized light field.…”
Section: Introductionmentioning
confidence: 99%
“…These experiments, in which a dielectric liquid (such as water or carbon tetrachloride) is excited by a short-duration ( ≈ 100 − 150 fs), highintensity ( ≈ 1 × 10 8 − 4 × 10 8 W/cm 2 ) electromagnetic pulse, have shown that the scattered, freeemitted light in the propagation direction orthogonal to that of the incident light, has a significant intensity in the polarization direction orthogonal to the incident polarization. These results, suggestive of magnetic dipole radiation patterns, have led to the theory that intense optical fields induce magnetism in individual molecules, that lead to the generation of significant transverse free currents, which in turn generate the observed radiation patterns [9][10][11][12]. This "transverse optical magnetism" theory has encountered a number of criticisms, primarily centered around the need for a large relative magnetic permeability μ r ≈ c for agreement with experiments [9,10,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%